CLINICAL CHARACTERISTICS OF BONE DEFECTS IN PERIPROSTHETIC INFECTION OF THE HIP JOINT - Tanasiienko, Pavlo; Kolov, Gennadiy; Kozak, Roman (Eastern Ukrainian Medical Journal, 2026)
The purpose of this analysis was to describe and characterize bone defects that were detected in patients of the observation array to unify the diagnostic algorithm, which will allow comparing the effectiveness of two-stage tactics of treating periprosthetic infection in different groups of patients.Materials and methods: A prospective array was formed, which included 117 patients, who were divided into 2 groups. To the first experimental group, we assigned 53 patients with early (up to 4 weeks) onset of the infectious process after primary hip arthroplasty. To the second group, 42 cases of late manifestation of periprosthetic infection were assigned.Results: The absence of bone defect or type I was significantly more common among patients with early development of periprosthetic infection, which was detected in 66.0% of patients and in 35.7% of patients with late development of periprosthetic infection. All types of type II defects were more common in patients with late development of periprosthetic infection, which was found in 52.4% of cases, in contrast to patients with early manifestation of periprosthetic infection, where this type was found in 33.9% of cases. Both types of type III bone defects were found only among patients with late periprosthetic infection, which was found in 11.9% of cases and were not found among patients with early manifestation of infectious prosthesis. Absence or type I bone defect was observed in most patients with early periprosthetic infection, which was found in 84.9% of cases and in most patients with late periprosthetic infection in 73.8% of cases. The distribution of type II bone defects of the hip was uniform in the observation groups, which indicates the absence of the influence of time determinants in the development of this type of bone defect. In the early stages of periprosthetic infection development, there are no severe types of bone defects, however, in patients with late manifestation, these defects were detected in 11.9% of cases.Conclusions: Different types of bone defects are characteristic of different periods of periprosthetic infection. Early manifestations of periprosthetic infection are characterized by either the absence of bone defects or the first type of them. The distribution of type II bone defects of the thigh was uniform in the observation groups, which indicates the absence of the influence of time determinants in the development of this type of bone defect.